2021
DOI: 10.1515/bmc-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin loaded magnetism nanoparticles based on cyclodextrin dendritic-graphene oxide inhibited MCF-7 cell proliferation

Abstract: Doxorubicin (DOX) is an effective chemotherapeutic agent used for the treatment of various types of cancer. However, its poor solubility, undesirable side effects, and short half-life have remained a challenge. We used a formulation based on graphene oxide as an anticancer drug delivery system for DOX in MCF-7 breast cancer cells, to address these issues. In vitro release studies confirmed that the synthesized formulation has an improved release profile in acidic conditions (similar to the tumor microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Moreover, our results are advantageous over that from [ 65 ], in which magnetic nanoparticles were prepared based on cyclodextrin dendritic-graphene oxide as nanocarriers for Dox, with a drug loading capacity of only 9.8%, while our Dox-PCL nanocapsules showed a higher drug loading capacity reaching 16.88%. Moreover, our results are significant to [ 66 ], showing that the in vitro release rate of Dox from selenium nanoparticles (SeNPs) decorated with hyaluronic acid (HA), HA-SeNPs nanoparticles, was up to 76.9% at 30 h. Nevertheless, the release rate of Dox in PBS at pH 7.4 was about 53.5%. Our results are advantageous over that of [ 67 ], who prepared a magnetic iron oxide nanoparticles (IONPs) stabilized with trimethoxysilylpropyl-ethylenediamine triacetic acid (EDT) were developed as a nanocarrier for anticancer drug doxorubicin, with drug loading capacity of only 5 ± 0.05%, while our dox-PCL nanocapsules showed a higher drug loading capacity reaching 16.88%.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, our results are advantageous over that from [ 65 ], in which magnetic nanoparticles were prepared based on cyclodextrin dendritic-graphene oxide as nanocarriers for Dox, with a drug loading capacity of only 9.8%, while our Dox-PCL nanocapsules showed a higher drug loading capacity reaching 16.88%. Moreover, our results are significant to [ 66 ], showing that the in vitro release rate of Dox from selenium nanoparticles (SeNPs) decorated with hyaluronic acid (HA), HA-SeNPs nanoparticles, was up to 76.9% at 30 h. Nevertheless, the release rate of Dox in PBS at pH 7.4 was about 53.5%. Our results are advantageous over that of [ 67 ], who prepared a magnetic iron oxide nanoparticles (IONPs) stabilized with trimethoxysilylpropyl-ethylenediamine triacetic acid (EDT) were developed as a nanocarrier for anticancer drug doxorubicin, with drug loading capacity of only 5 ± 0.05%, while our dox-PCL nanocapsules showed a higher drug loading capacity reaching 16.88%.…”
Section: Discussionsupporting
confidence: 67%
“…The results are reported in Table 1 and substantiate the previous findings in the literature. 49 As given in Table 1, the amounts of LE% and LC% for DOX in the prepared Fe 3 O 4 -ßCD nanoparticles are 96.73 ± 0.5 and 12.67 ± 0.11, respectively. Similarly, Mihanfar and colleagues designed and fabricated magnetic nanoparticles based on cyclodextrin dendritic graphene oxide containing DOX to suppress the breast cancer cells.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, Mihanfar and colleagues designed and fabricated magnetic nanoparticles based on cyclodextrin dendritic graphene oxide containing DOX to suppress the breast cancer cells. Based on their findings, the amount of DOX encapsulated within the developed nanoparticles was less than 10% with a LE of 98.13%, which supports well our results, 49 whereas by addition of Pep42 to Fe 3 O 4 -ßCD, the amounts of both LE% and LC% decreased, but this amount was still efficient and enough to tackle the cancer disease. Furthermore, in 2021, Loṕez-Munõz et al prepared polymeric nanoparticles containing DOX.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the DOX-loaded nano-carrier improved the cytotoxic effects of the DOX on the breast cancer cell lines, as compared to the free-DOX alone. These results introduced the possibility of a DOX-loaded carrier as a potential platform for in vitro targeting of breast and other cancer cells [ 104 ]. The GO was combined with the SPIONs, which were found to be biocompatible for magnetically driven drug delivery system, and they were also useful as a magnetic resonance contrast agent for MRI.…”
Section: Dox Delivery: Spions’ Polymeric Monomeric and Miscellaneous ...mentioning
confidence: 99%